2020
DOI: 10.1038/s41420-020-00305-y
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles in cardiovascular diseases

Abstract: Due to the continued high incidence and mortality rate worldwide, there is still a need to develop new strategies for the prevention, diagnosis and treatment of cardiovascular diseases (CVDs). Proper cardiovascular function depends on the coordinated interplay and communication between cardiomyocytes and noncardiomyocytes. Extracellular vesicles (EVs) are enclosed in a lipid bilayer and represent a significant mechanism for intracellular communication. By containing and transporting various bioactive molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
87
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(88 citation statements)
references
References 71 publications
0
87
0
1
Order By: Relevance
“…Although initially considered as inert cellular debris, EVs are now recognized as being important mediators in intercellular communication and many biological processes [ 31 , 32 , 66 ]. It has been shown that the concentration, composition, and cellular origin of EVs in body fluids differ between healthy subjects and patients suffering from diseases such as cancer, and cardiovascular and inflammatory diseases [ 31 , 67 , 68 , 69 , 70 , 71 , 72 ]. Therefore, there is a growing scientific and medical interest in EVs as valuable biomarkers in diagnostics and as therapeutics.…”
Section: Ev Subtypes Biogenesis and Their Biological Potentialsmentioning
confidence: 99%
“…Although initially considered as inert cellular debris, EVs are now recognized as being important mediators in intercellular communication and many biological processes [ 31 , 32 , 66 ]. It has been shown that the concentration, composition, and cellular origin of EVs in body fluids differ between healthy subjects and patients suffering from diseases such as cancer, and cardiovascular and inflammatory diseases [ 31 , 67 , 68 , 69 , 70 , 71 , 72 ]. Therefore, there is a growing scientific and medical interest in EVs as valuable biomarkers in diagnostics and as therapeutics.…”
Section: Ev Subtypes Biogenesis and Their Biological Potentialsmentioning
confidence: 99%
“…Circulating EVs are released by almost all cells, including cardiovascular system-related cells (e.g., blood, heart, and blood vessels) [ 24 , 25 ]. Biologic fluids, such as blood [ 26 ], urine [ 27 ], saliva [ 28 ], breast milk [ 29 ], and seminal fluid [ 30 ], as well as conditioned media from cell culture experiments [ 31 , 32 ], all contain EVs.…”
Section: Origins Of Extracellular Vesicles Related To Cvdmentioning
confidence: 99%
“…93,94 EVs are implicated in intercellular communication in both healthy and disease states. [95][96][97][98] They act as vehicles for the intercellular transfer of bioactive membranous and cytosolic molecules such as proteins, lipids, and various types of RNAs. [99][100][101] EVs can be isolated from various body fluids such as blood, urine, saliva, tears, seminal fluid, cerebrospinal fluid, and malignant ascites.…”
Section: Cd9 and Extracellular Membrane Vesiclesmentioning
confidence: 99%